IMPLEMENTASI MODEL JIGSAW BERBANTU GOOGLE SITES UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI SEJARAH PROKLAMASI KEMERDEKAAN DI KELAS VI - Indri Deniawati; Aura Setya Maharani; Haidar Akmal Ghifari; Septy Dewi Clara Sitorus; Zahra Aulia; Rana Gustian Nugraha (LPPM Universitas Cipta Mandiri, 2026)
This study was motivated by the low level of understanding among sixth-grade students of the material on the events leading up to the Proclamation of Indonesian Independence in the Social Sciences subject, particularly in terms of remembering the sequence of events and important figures. This condition has an impact on the low learning outcomes of students. This study aims to improve learning outcomes through the application of the Jigsaw learning model assisted by Google Sites media. The method used was Classroom Action Research, which was carried out in two cycles, consisting of the planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests and observation of student activities during learning. The results showed an increase in student understanding after the action was implemented. In cycle I, the average student score was 70, and there were still students in the low category. After improvements were made in cycle II through simplification of the material and optimization of Google Sites media, all students achieved a sufficient to very high category, with the average score increasing to 78.76. The integration of the Jigsaw model and digital media made learning more interactive, focused, and easier for students to understand. Thus, the use of the Jigsaw model assisted by Google Sites is effective in improving student learning outcomes in social studies material in elementary school.